The Mediating Role of Job Satisfaction between Strategic Performance Measurement System and Lecturers’ Performance in Malaysian Research University - Effendy Janudin, Sharul; Abdul Halim, Hazianti (International Journal of Engineering and Technology, 2018)
University’s lecturers play an important role to develop its human capital to be competitive and subsequently achieve world-class status. Unfortunately, research on measuring performance of university at the lecturer level are lacking due to difficulty to measure university input and output. Resource Based View theory and Work Performance Model were used in developing the research framework. The relationship between strategic performance measurement system (SPMS) and job satisfaction on lecturers’ work performance at the individual level was investigated through analysis on data gathered from 362 lecturers from five Malaysian research universities. Findings show 1) strategic performance measurement system has significant relationship with lecturers’ performance; 2) job satisfaction has significant relationship with lecturers’ performance; 3) job satisfaction fully mediates the relationship between strategic performance measurement system and lecturers’ performance.